Peningkatan Pengetahuan Ibu tentang Imunisasi Dasar melalui Leaflet di UPTD Puskesmas Cigandamekar - Rodi Roklis; Risna Nurlia; Enung Nur’Aisah; Aida Oktaviani (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Completing the full course of basic immunizations is an effective measure for preventing vaccine-preventable diseases. However, some mothers still possess limited knowledge regarding the benefits and schedules of immunization. This community service activity aimed to enhance mothers' knowledge through health education using leaflets within the service area of the Cigandamekar Community Health Center (UPTD Puskesmas) in Kuningan Regency. The methods employed included problem identification, leaflet development, the delivery of health education, and evaluation using pre-tests and post-tests. The results demonstrated an increase in participants' knowledge following the session. The leaflets helped participants understand the benefits, schedules, and importance of completing the full basic immunization course. This activity indicates that health education using leaflets is an effective health promotion method for increasing mothers' knowledge, thereby supporting the success of the full basic immunization program.